Perencanaan Area Nista Mandala Pura Samuan Tiga Bedulu Blahbatuh Gianyar Bali - Mahardika, Wayan Fajar; Sugianthara, Anak Agung Gede; Sukewijaya, I Made (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024, 2024)
Planning for the Nista Mandala Temple at Samuan Tiga Bedulu Temple, Blahbatuh, Gianyar , Bali. This research is motivated by the lack of order in the Nista Mandala area of ??Pura Samuan Tiga. This study aims to identify biophysical and socio-cultural aspects in the Nista Mandala area, as well as to plan a good holy place area at Nista Mandala Pura Samuan Tiga. The method used in this research is survey method with data collection techniques through observation, interviews, and literature study. The stages to determine the planning of the Nista Mandala Pura Samuan Tiga area use the stages of landscape planning, namely inventory, analysis, synthesis, basic concepts, planning stages and site plans. Based on the results of the inventory, analysis and synthesis obtained through the survey results produce recommendations for site plans, layouts and updates to the biophysical conditions of the site. The results of the study show that there are many conflicts in the function of the area so that the area needs to be reorganized. Spatial planning that has not been good in particular is the trading and parking area. The concept and function of space is determined using a diagram of the relationship between spaces. The concept of vegetation is planned to green the area by multiplying shade plants. The concept of circulation and facilities was developed in accordance with the space and activity needs in the Nista Mandala area of ??Pura Samuan Tiga. The final result is a site plan for landscape planning for the Nista Mandala Pura Samuan Tiga area.